Smart-recycling technology for construction waste in furniture design training - Nadezda S. Zhdanova; Anna V. Ekaterinushkina; Julia S. Antonenko (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper reviews the results of the creative team of teachers and students to explore the possibilities of recycling some construction waste. The analysis of publications in the sphere of ecological design testifies to the constant search of ways of recycling of different types of waste. The authors have focused their attention on the potential of using construction waste, the amount of which increases every year. The purpose of the study is to teach students to design furniture objects using recycled plastic pipes through educational Smart-technologies. The use of new Smart-technologies guarantees the achievement of the desired result. Their implementation was carried out in a distributed learning environment in stages. Preparatory stage: study of environmental problems and ways to overcome them, characteristics of construction waste, production and disposal of plastic pipes and existing ways of their recycling. Experimental stage: the study of plastic as a material for the manufacture of pipes, the technology of their manufacture, methods of connection; the development of an artistic and imaginative concept of furniture sets using plastic pipes. The final stage: the study of the possibilities of the project; the production of a prototype of the product in full size. The results of the study can be viewed from two positions: pedagogical and technological. From a pedagogical point of view, it is the promotion of students consciousness in the field of environmental design. From the technological point of view the formulation of methodological recommendations for the design of high-quality products from secondary raw materials.